Is online learning a win-win solution? The teachers and students’ stories - Febrianus Jordyan Kalanit; Sekar Anggi Veronika (Universitas Muhammadiyah Malang, 2020)
Currently, the learning process in schools and universities has changed due to coronavirus or COVID-19. This paper aims to determine the challenges students face during online teaching and learning activities, how students overcome these challenges and teachers' perceptions of the success of online teaching and learning activities. This narrative research studies participants' stories to determine any unique aspects of the topic being researched. The subjects involved in this study were 165 Vocational High School students and 30 teachers. Data collection techniques using interviews, surveys, and observations. Data analysis was carried out descriptively with data triangulation techniques for further clarification and exploration. Research findings indicate that students have both technical and cognitive challenges. They mostly solve the problems they face by discussing their problems with teachers and peers. Regarding teacher perceptions, good communication and students' affective domain are needed so that online teaching and learning activities are successful.